Cognitive Priming During Warmup Enhances Sport and Exercise Performance: A Goldilocks Effect - Jesús Díaz-García; Ana Rubio-Morales; David Manzano-Rodríguez; Tomás García-Calvo; Christopher Ring (Brain Sciences)
Background: Mental fatigue can impair sport, exercise and cognitive performance. Warmup activities can improve performance when the individual is rested. However, their effectiveness when the individual is fatigued has yet to be established. The research objectives were to evaluate the effects of physical and combined physical plus cognitive warmup activities on subsequent sport, exercise, and cognitive performance when rested and fatigued by sleep restriction in athletes (Study 1) and older adults (Study 2). Methods: In Study 1, 31 padel players completed a padel performance test and Stroop task after physical and combined warmups when rested and fatigued by sleep deprivation. In Study 2, 32 older adults completed sit–stand, arm curl, walking, Stroop, and psychomotor vigilance tests after no warmup, physical warmup, and combined warmup when rested and fatigued by sleep deprivation. In both studies, combined warmups intermixed short-, medium-, or long-duration cognitive tasks between physical warmup activities. Mental fatigue was measured using visual analog scale ratings. Results: In both studies, sleep deprivation increased mental fatigue and impaired performance. In Study 1, relative to a physical warmup, padel and Stroop performance were improved by combined warmups (with short-to-medium cognitive tasks) when rested and fatigued. In Study 2, relative to no warmup, sit–stand, arm curl, walking, Stroop, and reaction time performance were improved by physical and combined warmups (with short-to-medium cognitive tasks) when rested and fatigued. Conclusions: The negative effects of sleep deprivation on sport, exercise, and cognitive performance were best mitigated by combined warmups with short-to-medium cognitive tasks. Combined warmups are effective countermeasures against the deleterious effects of mental fatigue on performance.